2019
DOI: 10.1109/access.2019.2911526
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the GPS Spoofing Vulnerability in the Drone 3DR Solo

Abstract: At present, the boom in unmanned aerial vehicles (UAV) has been increasing in recent years, placing them in an important way in the commercial market. The use of UAV in the daily tasks of industry, commerce or as entertainment for children and adults becomes more recurrent. Each of the UAVs has a specific task, depending on the technologies that are provided, in addition to their basic functions with which they were manufactured. However, in most cases the security of these UAVs is not usually taken into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…When an intruder uses Telnet, he could directly access the drone system to manipulate important system files and Shellcode script using Parrot to disrupt the system [42]. In a specific situation, the intruder can restart the drone in full, deactivating the drone's engines that triggers a drop on the ground [43].…”
Section: Telnetmentioning
confidence: 99%
“…When an intruder uses Telnet, he could directly access the drone system to manipulate important system files and Shellcode script using Parrot to disrupt the system [42]. In a specific situation, the intruder can restart the drone in full, deactivating the drone's engines that triggers a drop on the ground [43].…”
Section: Telnetmentioning
confidence: 99%
“…In 2016, another incident of UAV deception through GPS spoofing attack, was reported in which a US custom bureau's UAV was targeted by Mexican drug dealers and traffickers (Khan, Brohi & Jhanjhi, 2020). Moreover, similar GPS based spoofing attacks have also been demonstrated in several other works (Dey et al, 2018;Horton & Ranganathan, 2018;Arteaga et al, 2019;He & Qiao et al, 2019;He & Liu et al, 2019;Ma et al, 2020;Zheng & Sun, 2020) against Hornet Mini, DJI's Matrice 100, Phantom 3 and 4 Pro, 3DR Solo, Parrot's AR Drone 2.0 and Bebop 2 drones.…”
Section: Introductionmentioning
confidence: 85%
“…However, different research efforts have shown that GPS signals can be jammed or spoofed owing to its inherent vulnerabilities. Because of the low signal power (around −130 dBm), the GPS services can easily be disrupted through the transmission of high power jamming signals directed towards the victim platform ( Arteaga et al, 2019 ). Besides, the civil GPS services have no encryption or authentication mechanisms and therefore, the satellite signals can easily be replicated or fabricated, which can subsequently be utilized for launching sophisticated GPS spoofing attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Ullah et al [23] investigated the benefits of uses of 5G in various domains by considering several use cases. Arteaga et al [2] presented an exploitation of the "Global Positioning System (GPS)" vulnerability in commercial drones. Their identified vulnerability could help a malicious attacker to control autonomy and carry out other illegal tasks.…”
Section: Related Workmentioning
confidence: 99%